Anterior Urethral Stricture Disease Negatively Impacts the Quality of Life of Family Members - Jonathan R. Weese; Valary T. Raup; Jairam R. Eswara; Stephen D. Marshall; Andrew J. Chang; Joel Vetter; Steven B. Brandes (Advances in Urology)
Purpose. To quantify the quality of life (QoL) distress experienced by immediate family members of patients with urethral stricture via a questionnaire given prior to definitive urethroplasty. The emotional, social, and physical effects of urethral stricture disease on the QoL of family members have not been previously described. Materials and Methods. A questionnaire was administered prospectively to an immediate family member of 51 patients undergoing anterior urethroplasty by a single surgeon (SBB). The survey was comprised of twelve questions that addressed the emotional, social, and physical consequences experienced as a result of their loved one. Results. Of the 51 surveyed family members, most were female (92.2%), lived in the same household (86.3%), and slept in the same room as the patient (70.6%). Respondents experienced sleep disturbances (56.9%) and diminished social lives (43.1%). 82.4% felt stressed by the patient’s surgical treatment, and 83.9% (26/31) felt that their intimacy was negatively impacted. Conclusions. Urethral stricture disease has a significant impact on the family members of those affected. These effects may last decades and include sleep disturbance, decreased social interactions, emotional stress, and impaired sexual intimacy. Treatment of urethral stricture disease should attempt to mitigate the impact of the disease on family members as well as the patient.